2015
DOI: 10.1038/srep18303
|View full text |Cite
|
Sign up to set email alerts
|

Development of a real-time flexible multiphoton microendoscope for label-free imaging in a live animal

Abstract: We present a two-photon microendoscope capable of in vivo label-free deep-tissue high-resolution fast imaging through a very long optical fiber. First, an advanced light-pulse spectro-temporal shaping device optimally precompensates for linear and nonlinear distortions occurring during propagation within the endoscopic fiber. This enables the delivery of sub-40-fs duration infrared excitation pulses at the output of 5 meters of fiber. Second, the endoscopic fiber is a custom-made double-clad polarization-maint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
114
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(117 citation statements)
references
References 50 publications
(69 reference statements)
0
114
0
1
Order By: Relevance
“…All of this information can be used to assess whether a tissue is normal, LGIN or HGIN. Moreover, SHG microscopy does not require staining and in the future could be applied in vivo in a clinical setting with multiphoton endoscopy (Fu et al, 2006;Le Harzic et al, 2008;Brown et al, 2012;Ducourthial et al, 2015). With continued improvement and refinement of this technique, we believe that second-harmonic imaging microscopy will be an efficient surveillance tool for colorectal intraepithelial neoplasia and lead to better management of these lesions.…”
Section: Discussionmentioning
confidence: 99%
“…All of this information can be used to assess whether a tissue is normal, LGIN or HGIN. Moreover, SHG microscopy does not require staining and in the future could be applied in vivo in a clinical setting with multiphoton endoscopy (Fu et al, 2006;Le Harzic et al, 2008;Brown et al, 2012;Ducourthial et al, 2015). With continued improvement and refinement of this technique, we believe that second-harmonic imaging microscopy will be an efficient surveillance tool for colorectal intraepithelial neoplasia and lead to better management of these lesions.…”
Section: Discussionmentioning
confidence: 99%
“…With such tools, the imaging depth can be increased to beyond 1 mm. 187 Alternatively, thicker samples can be imaged with a significant improvement in depth by twophoton or multiphoton microscopy 188,189 or prepared post-experiment to offer better imaging capabilities off-line (see Sec. IV D).…”
Section: Fluorescence Imagingmentioning
confidence: 99%
“…There is currently much interest in the potential usage of such instruments to perform 'virtual biopsies' in humans, whereby the histological nature of suspicious lesions could be assessed in situ [18]. It has recently been demonstrated that endoscopic microscopy can also be used to image the kidney in living anaesthetized mice [19], and although the quality of images that can be acquired is not as high as conventional MPM, this approach could clearly be advantageous for repetitive imaging studies in the same animal, perhaps even when awake.…”
Section: Microendoscopymentioning
confidence: 99%